Shared decision-making and the implementation of treatment recommendations for depression. Issue 8 (August 2021) - Crawford, Joanna; Petrie, Katherine; Harvey, Samuel B.
Abstract: Objective: This study aimed to examine the relationship between shared decision-making (SDM) and the implementation of treatment recommendations amongst outpatients at a specialist Depression Clinic. Methods: A total of 110 adult outpatients in a specialist Depression Clinic in Sydney, Australia, completed an online survey examining their experiences of shared decision-making (SDM) during their psychiatrist consultation and the extent to which they later implemented Depression Clinic treatment recommendations. Results: The odds of implementing treatment recommendations were over four times higher in patients who reported a high level of SDM in their consultation, compared to those who reported a low level of SDM. Further, three elements of patient-rated SDM were significantly associated with an increased likelihood of implementing depression treatment recommendations. These three elements were: i) being given the opportunity to ask questions or voice concerns; ii) being asked about any problems or side effects from previous treatments; and iii) being involved in deciding their treatment plan. Conclusions: SDM was significantly associated with an increased likelihood of implementing psychiatrists' treatment recommendations at a specialist Depression Clinic. Practice implications: : We recommend that clinicians be informed of the potential benefits of SDM and adopt SDM when developing treatment plans with patients living with depression.